The significance of the quality and quantity in the management of an organization = Znaczenie ilości i jakości w zarządzaniu organizacją - Jaremczuk, Kazimierz (Zielona Góra: Faculty of Economics and Management Press)
The article is an attempt to recognise the premises of quality in the management process by pointing to the consequences of reducing the description of an employee as a person to only quantitative categories. Focusing on the rational attitude in the management process may lead to creating an ideal image of the employee, who functions in a reality which is created by quantification and operationalisation. A dominant significance of quantitative knowledge means a domination of an unreal image of the person of an employee in the management process. This process may lead to a reification and primacy of the thing over the employee as a person, and therefore to omitting the various potentialities for activity of the subject, whose element is the reality in an organization and its environment.
Keywords: zarządzanie organizacją; jakość w zarządzaniu; wiedza ilościowa; ilość; management of organization; quality in the management; quantity in the management